1989
DOI: 10.1007/bf02562124
|View full text |Cite
|
Sign up to set email alerts
|

Perforation of the rectum and sigmoid colon during barium-enema examination

Abstract: Perforation of the rectum or sigmoid colon complicated 5 of 2200 barium-enema examinations performed during a 4-year period. Three patients with rectal perforations manifested by air extravasation were successfully treated with intravenous antibiotics and complete bowel rest. Two patients with barium extravasation were treated with immediate operation and colostomy. All five patients recovered. Perforation was found to be associated with a rectal stricture due to ulcerative colitis, a rectal cancer, an incarce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
4

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 17 publications
0
30
0
4
Order By: Relevance
“…Terranova et al 3 reported that this complication occurred in 1% of all barium studies. In the study of Fry et al 4 rectum or sigmoid colon perforations were found in 5 cases among the 2200 barium-enema examinations performed during a 4-year period.…”
Section: Discussionmentioning
confidence: 94%
“…Terranova et al 3 reported that this complication occurred in 1% of all barium studies. In the study of Fry et al 4 rectum or sigmoid colon perforations were found in 5 cases among the 2200 barium-enema examinations performed during a 4-year period.…”
Section: Discussionmentioning
confidence: 94%
“…[35][36][37] Barium enema pressures of around 40 mmHg are necessary to perform an adequate double contrast study. 20,22,38 Human studies have shown that the luminal pressure needed to perforate the colon is higher than that: lowest in the cecum, and highest in the rectum. The risk increases with biopsies that involve the muscularis propria, which is unusual for routine biopsies.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 The rate of colon perforation for colonoscopy is 0.03 to 1% for diagnostic and 0.2% for therapeutic procedures with 0.0009% mortality, and 0.02 to 0.24% for DCBE with 0.07% mortality. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] A recent metaanalysis by Bellini et al of the rate of CTC perforation in 103,399 patients indicates a perforation rate of 0.04% (95% confidence interval (CI) 0-0.10; I 2 ¼ 29.1%) or one in 2500 studies. 19 Some centers wait days to perform a DCBE following an incomplete colonoscopy with biopsy because of concerns about causing a perforation as a result of the pneumatic pressure and resultant tension on the colon wall from the injection of barium, even though data to support this concern are not robust.…”
Section: Introductionmentioning
confidence: 99%
“…In treatment of iatrogenic colonic perforation, nonoperative management of colonic perforation is advocated for patients who are clinically stable with no evidence of peritonitis [8][9][10] . For selected patients with incidental intramural or small retroperitoneal perforations but no evidence of barium spillage, favorable results have also been reported as the result of conservative treatment consisting of bowel rest combined with total parenteral nutrition, intravenous fluid treatment, and broad-spectrum antibiotics [11,12] .…”
Section: Discussionmentioning
confidence: 99%